Postgraduate Education of Allied Physicians for Innovation Technologies for Nursery Care, Diagnostics and Pathology Treatment - T.M. Klimenko; T.V. Sandulyak; Ye.A. Serdtseva; O.Yu. Karapetyan; A.M. Zakrevsky (Zaslavsky O.Yu., 2012)
The possibilities and positive results of the postgraduate education of allied physicians on neonatology at the specialized department as well as studying innovation technologies of caring, diagnostics and treatment of newborn pathology are considered.